2016
DOI: 10.2147/cpaa.s100521
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-, and positive-controlled clinical pilot study to evaluate the efficacy and tolerability of standardized aqueous extracts of Terminalia chebula and Terminalia bellerica in subjects with hyperuricemia

Abstract: ObjectivesTo evaluate the efficacy and tolerability of standardized aqueous extracts of Terminalia chebula and Terminalia bellerica versus febuxostat and placebo on reduction in serum uric acid levels in subjects with hyperuricemia.Materials and methodsA total of 110 eligible subjects with hyperuricemia were enrolled and randomized to either of the five treatment groups – T. chebula 500 mg twice a day (BID), T. bellerica 250 mg BID, T. bellerica 500 mg BID, placebo BID, and febuxostat 40 mg once daily plus an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In a previous study [11] done at our department, we have reported that T. bellerica inhibited uric acid formation, which was indicative of its xanthine oxidase enzyme inhibitory activity. In our present study, it is observed that serum uric acid and serum creatinine levels have significantly improved, which in turn has led to the improvement in estimated glomerular filtration rate with all the treatment groups.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In a previous study [11] done at our department, we have reported that T. bellerica inhibited uric acid formation, which was indicative of its xanthine oxidase enzyme inhibitory activity. In our present study, it is observed that serum uric acid and serum creatinine levels have significantly improved, which in turn has led to the improvement in estimated glomerular filtration rate with all the treatment groups.…”
Section: Discussionmentioning
confidence: 74%
“…The commonly preferred agents in both overproducers and under-secretors of uric acid include xanthine oxidase (an enzyme involved in the synthesis of uric acid) inhibitors such as allopurinol and febuxostat [10]. In our previous study, we have demonstrated that Terminalia bellerica (TB) significantly decreased serum uric acid levels with no serious adverse effects, thus showing its xanthine oxidase inhibiting property and potential for the treatment of hyperuricemia [11]. Considering this, we carried out the present study to evaluate the effect of TB when compared to febuxostat in preventing the progression of CKD in subjects with hyperuricemia.…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that Terminalia chebula has been used in other clinical trials for treating hyperuricemia (Usharani, Nutalapati, Pokuri, Kumar, & Taduri, 2016), decreasing cardiovascular risk factors in patients with type 2 diabetes mellitus (Pingali, Sukumaran, & Nutalapati, 2020), and improving joint mobility in healthy overweight subjects (Lopez et al, 2017). The reported adverse effects in the previous studies were mild gastrointestinal intolerance, dyspepsia, and cramps (Lopez et al, 2017; Pingali et al, 2020; Usharani et al, 2016). But in the present study, increased libido, dry mouth, colic, and confusion were found as adverse effects of black myrobalan.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,9,10 Due to its anti-ageing activity, it is recommended for the promotion of health in elderly. Hypoglcaemic effect and hypolipidemic effect 11 Anti-oxidant effect 12 Anti arthritic activity 13,14 Neuroprotective effect 15 Antigastritis effect 16 Hypourecemic effect 17 improving gastrointestinal motility 18 Cardiotonic activity , 19,20 Hepatoprotective effect 21…”
Section: Actions and Usesmentioning
confidence: 99%